The Effect Of Biorafia Fiber Density On The Decrement Of Pb And Cr In Sail River’s Water - Mira Kurnia Irde; Budijono Budijono; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTOne of the pollutants that insert to the Sail River is a heavy metal. The effort that will the researcher do to reduce the level of heavy metal (Pb and Cr) is using the biocord. Biocord is a rope from the three-dimension of woven fine fiber that can hold the microorganisms in a large quantity. This research uses the raffia media so that this research names biorafia. This research aims to determine the effect of biorafia density toward the decreasing level of heavy metal such as Pb and Cr on the water of the Sail River. This research has done in March - April 2019. In this research, the researcher uses a completely randomized design (CRD) method using 3 treatment levels, and 3 replications. 3 treatment levels of biorafia density are P1 (rare), P2 (moderate), and P3 (dense). The result shows us a decreasing level of heavy metal such as Pb and Cr. The decreasing values of the heavy metal level of Pb are P1 (0.071 mg / L), P2 (0.074 mg / L), and P3 (0.073 mg / L). Also, the decreasing values of the heavy metal level of Cr are P1 (0.055 mg / L), P2 (0.056 mg / L), and P3 (0.055 mg / L).Keywords:Biorafia density, heavy metals, lead, chromium